An ultrasonic sealing method and an ultrasonic sealing apparatus - Ninomiya, Akihide; Yamamoto, Hiroki; Nakano, Takumi (2019)
SUBJECT of the Invention It exists in suppressing that the quality of a seal part (S) deteriorates. PROBLEM to be solved It is an ultrasonic sealing method which forms several seal part (S) in the conveyance direction of a continuous web (30) at intervals by repeatedly performing an ultrasonic sealing process with respect to the continuous web (30) which concerns on the absorbent article conveyed, Comprising: The anvils (14) of the said ultrasonic sealing process are an ultrasonic horn (8) and the clamping process of clamping a continuous web (30), The seal part formation process which forms a seal part (S) in a continuous web (30) when an ultrasonic horn (8) vibrates in response to the ultrasonic wave which an ultrasonic wave generator (9) emits, The unclamping process of which clamping of a continuous web (30) is cancelled|released, It has these, In a seal part formation process, An ultrasonic wave generator (9) emits an ultrasonic wave so that time until it finishes emitting, since it begins to emit an ultrasonic wave may become longer than the cycle period of the said ultrasonic sealing process, The ultrasonic sealing method characterized by the above-mentioned. SELECTED DRAWINGS FIG. 10